Acute Toxoplasma Gondii Infection in Cats Induced Tissue-Specific Transcriptional Response Dominated by Immune Signatures - Cong, Wei; Dottorini, Tania; Khan, Faraz; Emes, Richard D.; Zhang, Fu-Kai; Zhou, Chun-Xue; He, Jun-Jun; Zhang, Xiao-Xuan; Elsheikha, Hany M.; Zhu, Xing-Quan (Frontiers in Immunology, 2018)
We used RNA-sequencing to detect transcriptional changes in six tissues of cats 7 days after T. gondii infection. 737 genes were differentially expressed (DEGs), of which 410 were up-regulated and 327 were down-regulated. The liver exhibited 151 DEGs, lung (149 DEGs), small intestine (130 DEGs), heart (123 DEGs), brain (104 DEGs), and spleen (80 DEGs) – suggesting tissue-specific transcriptional patterns. Gene ontology and KEGG analyses identified DEGs enriched in immune pathways, such as Toll-like receptor signaling pathway and NF-kappa B signaling pathway. PI3K/Akt expression was down-regulated in all tissues except the spleen. The genes for phosphatase, indoleamine 2,3-dioxygenase, Hes Family BHLH Transcription Factor 1, and guanylate-binding protein 5 - playing various roles in immune defence - were co-expressed across various tissues. K-means clustering analysis produced seven gene clusters with significant co-expression patterns associated with single tissues, with lung tissue cluster having the largest number of genes. These findings revealed that a broad immune defence capacity responding to T. gondii infection exists within various tissues in cats.